Sex-specific adipose tissue’s dynamic role in metabolic and inflammatory response following peripheral nerve injury - Valentina Vacca; Claudia Rossi; Luisa Pieroni; Federica De Angelis; Giacomo Giacovazzo; Ilaria Cicalini; Domenico Ciavardelli; Flaminia Pavone; Roberto Coccurello; Sara Marinelli (iScience, 2023)
Summary: Epidemiological data and research highlight increased neuropathy and chronic pain prevalence among females, spanning metabolic and normometabolic contexts, including murine models. Prior findings demonstrated diverse immune and neuroimmune responses between genders in neuropathic pain (NeP), alongside distinct protein expression in sciatic nerves. This study unveils adipose tissue’s (AT) role in sex-specific NeP responses after peripheral nerve injury. Metabolic assessments, metabolomics, energy expenditure evaluations, AT proteomic analyses, and adipokine mobilization depict distinct AT reactions to nerve damage. Females exhibit altered lipolysis, fatty acid oxidation, heightened energy expenditure, and augmented steroids secretion affecting glucose and insulin metabolism. Conversely, male neuropathy prompts glycolysis, reduced energy expenditure, and lowered unsaturated fatty acid levels. Males’ AT promotes regenerative molecules, oxidative stress defense, and stimulates peroxisome proliferator-activated receptors (PPAR-γ) and adiponectin. This study underscores AT’s pivotal role in regulating gender-specific inflammatory and metabolic responses to nerve injuries, shedding light on female NeP susceptibility determinants.